Feminist ethnography as ‘Troublemaker’ in educational research: analysing barriers of social justice - Lappalainen Sirpa; Hakala Katariina; Lahelma Elina; Mietola Reetta; Niemi Anna-Maija; Salo Ulla-Maija; Tolonen Tarja (Routledge, Taylor & Francis Group, 2022)
The focus of this article is on the history and current trends of feminist ethnography in Finland. It highlights the impact of feminist ethnography in Finnish educational research and illustrates how feminist ethnography has succeeded in asking novel questions and developing methodologies by drawing on multiple feminist theories. The article is based on a review of studies, selected to represent the multiplicity of themes, theoretical approaches and methodological epiphanies, as well as earlier analyses and memories of researchers who launched feminist educational ethnography in Finland. Drawing predominantly from the British feminist educational ethnography, in Finland feminist ethnography in education took its first steps in the 1990s and achieved a stable position in the early 2000s. Feminist ethnography has contributed to a debate on social justice by highlighting the hidden modes of discrimination and exclusion in educational institutions, thus ‘troubling’ the national self-image as a forerunner of equality and social justice.